Perception of university students on Facebook - Lim, Wei Siang; Abu al-Rejal, Hussein Mohammed (Universiti Utara Malaysia, 2020)
The research is to study the perception of students on Facebook. The objective of this study is to identify the influence of usefulness, ease of use, social influence, facilitating conditions and community identity on Facebook adoption. Identify the influence of social relations, work-related purpose, and daily activities influence on the purpose of Facebook usage. Identify the influence of communication, collaboration and resources and material sharing on the educational usage of Facebook. Identify the relationship between Facebook adoption with the purpose of Facebook usage. Identify the relationship between the purpose of Facebook usage with the educational usage of Facebook and identify the relationship between Facebook adoption mediated by the purpose of Facebook usage with the educational usage of Facebook. Quantitative approach is using to get the results from students of STML. The result show that the relationship is positive between the adoption, purpose and educational usage of Facebook.